In-Depth Analysis and Identification of the Fully Intelligent Warfare Technology Fog - Fu Xiang, Huang Pei, Ye Yongkai, Zhang Ping, Wang Xiaolong (Editorial Office of Aero Weaponry, 2021)
The concept of “Mosaic Warfare”proposed by the Defense Advanced Research Projects Agency (DARPA) describes the main features and operational styles of the future fully intelligent warfare, which has been widely concerned by countries all over the world. So, for the current level of artificial intelligence technology, is there any technological fog and trap in the fully intelligent warfare represented by “Mosaic Warfare”? Where are the bottlenecks? To address these problems, this paper analyzes more than 50 typical military intelligence projects of the US army in the field of air operations in recent years, and extracts 10 typical capability characteristics of intelligent air operations. Then, this paper studies and combs 20 basic intelligence technology groups in the field of artificial intelligence, clarifies the overall architecture of artificial intelligence technology supporting the future fully intelligent operations, and points out the bottlenecks of fully intelligent warfare. On this basis, the focuses and directions in future military intelligence research are given.